The Voting Premium - LEVIT, DORON; MALENKO, NADYA; MAUG, ERNST (Journal of Finance, 2026)
ABSTRACT We develop a unified theory of blockholder governance and the voting premium in a setting without takeovers or controlling shareholders. A voting premium emerges when a minority blockholder can influence shareholder composition by accumulating votes and buying shares from dissenting shareholders. Our theory reconciles conflicting empirical findings by showing that standard measures of the voting premium often misrepresent the true value of voting rights, increased conflicts between the blockholder and small shareholders do not necessarily raise the voting premium, and the voting premium can even turn negative when small shareholders free‐ride on the blockholder's trades.